International journal of information technology and web engineering an official publication of the Information Resources Management Association. - IGI eBooks; IGI Global; Information Resources Management Association (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2006)
Organizations are continuously overwhelmed by a variety of new information technologies, many are Web based. These new technologies are capitalizing on the widespread use of network and communication technologies for seamless integration of various issues in information and knowledge sharing within and among organizations. This emphasis on integrated approaches is unique to this journal and dictates cross platform and multidisciplinary strategy to research and practice.
Also available in print.
Mode of access: World Wide Web.
Description based on: Vol. 1, issue 1, (2006); title from title screen (IGI Global, viewed Oct. 1, 2010).
Latest issue consulted: Vol. 5, issue 3, (2010).
Keywords: Information technology -- Periodicals; Web site development -- Periodicals; Case studies; Competitive intelligent information systems; Data analytics; Data and knowledge capture and quality issues; Data and knowledge validation and verification; Human factors and cultural impact; Information filtering for wireless devices; Display adaptation techniques for wireless devices; Integrated heterogeneous and homogeneous workflows and databases; Integrated user profile, provisioning, and context-based processing; IT education and training; Knowledge structure, classification, and search algorithms or engines; Metrics-based performance measurement; Mobile, location-aware, and ubiquitous computing; Ontology and Semantic Web studies; Quality of service and service level agreement issues among integrated systems; Radio frequency identification (RFID) research and applications in Web engineered systems; Security, integrity, privacy, and policy issues; Software agent-based applications; Strategies for linking business needs and IT; Virtual teams and virtual enterprises; Web systems architectures; Web systems engineering design; Web systems performance engineering studies; Web user interfaces design; Electronic books